Phosphogypsum resource utilization in road engineering: A brief review and development discussion - Zhu Hongming; Yin Yuan; Cheng Shufan (E3S Web of Conferences)
Phosphogypsum is the principal gypsum as a by-product. The hazards of too much PG accumulation have created an environmental crisis worldwide. In road engineering, it is requisite to probe into a new means of elevating the utilization rate of PG. Therefore, in this paper, the current situation of the PG materials and their main utilization was discussed. It was found that clean treatment of PG, including physical and chemical means can remove the main impurities in PG. Processed PG can be utilized in a variety of ways, and PG-based materials can consume large amounts of solid waste. Road fillers have a relatively large consumption potential for PG, but the utilization ratio stays at a lower level. Therefore, it is necessary to find a more comprehensive utilization method.